Survey on the current status of discharge readiness of parents of children with liver transplantation and analysis of influencing factors - He, Ting; Tang, Li Hua; Huang, Xiaobo; Sa'at, Siti Fatimah (Sanglah General Hospital, 2024)
Background: The objective of this study is to gain insight into the present state of discharge preparedness among parents of pediatric liver transplant recipients, as well as to examine the many variables that contribute to this readiness. Methods: This is a cross-sectional analytic study. The researchers employed a convenience sampling technique to gather data from 103 parents with children who underwent liver transplants. The data was collected using a general information questionnaire and a Chinese version of the Discharge Readiness Scale. To examine the factors that influenced the discharge readiness of parents in this population, the researchers conducted a multiple linear regression analysis. Results: The study found that the mean total readiness to discharge score for parents of children who underwent liver transplants was 83±35.5. Multiple linear regression analysis revealed that several factors significantly influenced the readiness to discharge of these parents. These factors included the average monthly family income, daily nursing hours, whether the child was an only child, and whether the child experienced postoperative complications. The statistical significance of these factors was determined to be P<0.05. Conclusion: The discharge preparedness of parents of pediatric liver transplant recipients is found to be poor, indicating a need for healthcare providers to adopt focused interventions aimed at enhancing the quality of discharge orientation services.